The Brazilian Federal Supreme Court and the issue of gender ideology in schools - Hennig Leal, Mônia Clarissa (2021)
On 23 June 2021, the Hungarian President Jánus Áder issued a law which forbids schools and the media from “promoting or portraying” homosexuality or sex reassignment to minors and limits sexual education in schools, a situation similar to that which was verified in Brazil, where a law project with identical purpose is being submitted to the National Congress (the proposition of Bill 246/2019), having also been the subject of municipal regulations, whose constitutionality was questioned in specific actions at the Brazilian Federal Supreme Court (ADPF 457/GO). This article intends to answer the following question: is there a (dis)alignment between the content in the Bill 246/2019 and the foundations used by the Brazilian Federal Supreme Court in the decision of the ADPF 457/GO? For that purpose, the importance of the current gender and sexual diversity approach in the school environment for the protection of sexual and gender minorities, under the perspective of the state duties of protection (Schutzpflicht), resulting from the objective dimension of the fundamental rights will be analysed. Next, the foundations used by the Brazilian Federal Supreme Court in the ADPF 457/GO will be evaluated, as well as the existence (or non-existence) of a difference between the foundations of the Federal Supreme Court and the text of the Bill. It was concluded that there is a difference in the position adopted by the two Powers, because the highest Brazilian Court understands such themes may be developed in the student’s pedagogical formation, while the Bill moves in the direction of sealing references to these themes in the school environment.